PENGARUH MOTIVASI BELAJAR, PRESTASI BELAJAR, STATUS SOSIAL EKONOMI ORANG TUA, DAN LINGKUNGAN TEMAN SEBAYA TERHADAP MINAT MELANJUTKAN PENDIDIKAN KE PERGURUAN TINGGI S1 AKUNTANSI PADA SISWA SMK SWASTA DI BANJARMASIN - Ruslinda Agustina; Rizki Amalia Afriana (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2018)
Abstract, This study aims to prove empirically the influence of learning motivation, learning achievement, socioeconomic status of parents and the environment of peers against the interests of private SMK students in Banjarmasin to continue education to S1 Accounting. The population in this study amounted to 206 students class XII accounting consisting of: SMK BINA BANUA, SMK MAESTRO, SMK NU, and SMK Muhammadiyah I. This study used primary data by distributing questionnaires to respondents (students) with the help of SPPS test tool version 16.00. The results of this study indicate that H1 is accepted because the motivation to learn can improve financial ability and become one of the decisions of a person to achieve higher formal education and gain direct or indirect award. While H2, H3, and H4 are not accepted because some students think they are able to perform and improve their ability to continue to college with the existing skill competencies for education expenses can be either government or corporate scholarships. They can get information about higher education not from friends but direct experience from family. The conclusion in this research is partially only H1 which influence to student's interest to continue to college S1 Accounting while H2, H3, and H4 have no effect. Simultaneously H5 effect on student interest to continue education to college S1 accounting.